The Why and How of Polymorphic Artificial Autonomous Swarms - Fabrice Saffre; Hannu Karvonen; Hanno Hildmann (Drones)
In this paper, we investigate the concept of polymorphism in the context of artificial swarms; that is, collectives of autonomous platforms such as, for example, unmanned aerial systems. This article provides the reader with two practical insights: (a) a proof-of-concept simulation study to show that there is a clear benefit to be gained from considering polymorphic artificial swarms; and (b) a discussion on the design of user-friendly human–machine interfaces for swarm control to enable the human operator to harness these benefits.